Implementasi Digital Signature Pada File Audio Menerapkan Metode SHA-256 - Endelina Endelina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
In an era of information technology that is growing very rapidly, the use of signatures has been implemented digitally through digital signatures. Digital signatures develop along with the emergence of the need to authenticate data or files that are used digitally. Its use also aims to avoid forgery or interference. Currently, the use of digital signatures has been widely applied to software distribution, financial transactions, and file delivery. The use of digital signatures on audio files can be accomplished by using encryption of messages sent with a key to use a combination of hash functions with public-key cryptography. This method can be used temporarily. The use of a digital signature in the form of an encrypted writing or a hash function will produce a signature document that is clearly visible because it is written in a visible code. This can lead to potential interference by removing the signature so that the document received is deemed not equipped with a digital signature.